High 28-day mortality in critically ill patients with sepsis and concomitant active cancer - Wang, Yong-gang; Zhou, Jian-cang; Wu, Kang-song (Journal of international medical research, 2018)
Objective This study was performed to explore the characteristics and outcomes of patients with sepsis accompanied by active cancer who were admitted to the intensive care unit (ICU). Methods The baseline characteristics, infection profiles, and outcomes of patients with sepsis were retrospectively analyzed according to the presence of concomitant active cancer. The association between concomitant active cancer and 28-day mortality was explored. Results Of 23,956 patients with sepsis, 1574 (6.6%) had concomitant active cancer. The most common type was digestive (30.7%). The 28-day mortality ranged from 41.9% to 81.5%. Patients with active cancer had a significantly higher Simplified Acute Physiology Score II and significantly shorter length of ICU stay. Respiratory (32.9%), genitourinary (31.0%), and bloodstream (17.0%) infections were most common. Escherichia coli was the most frequent gram-negative pathogenic bacteria. The 28-day mortality rate was significantly higher in patients with than without active cancer. Concomitant active cancer was associated with increased 28-day mortality in patients with sepsis. Hematological malignancy was associated with a significantly higher risk of death than solid tumors. Conclusions Concomitant active cancer was associated with higher 28-day mortality in patients with sepsis requiring ICU admission. Hematological malignancy was associated with a higher risk of death than solid tumors.